Evaluation of gross motor function before and after virtual reality application - Luiza da Silva Pereira Tannus; Danieli Isabel Romanovitch Ribas
Abstract Introduction: Recently virtual reality has been aggregated to the therapeutic possibilities for patients who need functionality gains, such as individuals with cerebral palsy (CP). Aim: to evaluate the effects of virtual reality on the gross motor function of individuals with CP. Methods: longitudinal study, realized in a special education school, with five individuals with CP (7.4 years of age ± 1.14) of both sexes, evaluated using the B, D and E dimensions of the GMFM 88, before and after the application of three Wii Fit Plus(r) console games: Hula Hoop, Slide Penguin and Soccer Heading. These games were applied for four minutes per game, at the beginner level, twice a week, for twelve consecutives weeks. The normality of the sample was evaluated through the Shapiro-Wilk's test. The results obtained before and after the Wii Fit(r) application were compared using descriptive statistics. Results: all the individuals obtained improvements in the dimensions evaluated after the virtual reality application, with a 5.14% general improvement, varying between 1.9% and 9.6%. The standing (D) and walking, running and jumping (E) dimensions were the dimensions which obtained higher improvement percentages. Conclusion: considering the study limitations, the results obtained suggest that virtual reality can promote benefits in the gross motor function of individuals with cerebral palsy.